Enhancing children's role as agents of change in the utilization of household medicinal plants - Wijaya, Dian Rezki; Zhahiirah, Andi Nur Shabaa; Lestari, Sri Ayu; Nurhasnina, Sitti; Syarif, Alwiyah Nur; Saleh, Syamsudhuha (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
The utilization of household medicinal plants (in Indonesia known as TOGA) as a form of local wisdom holds great potential for improving public health. However, its use as an alternative traditional treatment remains suboptimal, especially among the younger generation. TOGA not only serves as cooking ingredients but also offers natural and independent health benefits. Therefore, this empowerment activity aims to enhance students' knowledge and awareness of the benefits of TOGA through educational counseling and practical garden-making activities. The program was conducted on October 13-14, 2024, at SD Negeri 21 Rumbia, involving 52 students from grades 3, 4, and 6. The methods used included lectures, leaflet distribution, an interactive game called